Geotechnical characterisation of Hugo North Lift 1, Oyu Tolgoi - Rwodzi, L.; Ekkerd, J.; Taylor, M.; Batsaikhan, A.; Russo, A.; Ramírez, C.; Hormazábal, E.; Nur, J. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Most major block cave operations in the world are hosted in porphyry orebodies, which pose significant geotechnical characterisation challenges due to their heterogenous and hydrothermally altered nature. The Hugo North Lift 1 block cave at Oyu Tolgoi is a large-footprint, deep cave hosted within a structurally complex porphyry system subjected to high stresses and exhibiting moderate to low strength rock mass conditions. A comprehensive geotechnical block model covering the multiple production blocks at Oyu Tolgoi was developed over several years. Geotechnical units were defined using lithology, alteration, weak veinlet density and fault models, supplemented by drillhole composites. Fundamental rock mass characterisation parameters obtained from drillcore logging and underground tunnel mapping were estimated using statistical and geostatistical methods to populate the geotechnical block model. Extensive intact rock strength testing was also undertaken to inform the Hoek–Brown rock strength parameters adopted into the block model, and a dedicated methodology was developed to capture fault strength properties. The resulting characterisation workflow and integrated block model have directly supported improved inputs into footprint stability assessments, fragmentation predictions, caveability and subsidence assessments, and have reduced geotechnical uncertainty in Hugo North Lift 1 design and sequencing. This paper presents the characterisation methodology, resulting geotechnical insights for this complex porphyry orebody, and highlights key lessons learnt.